16S rRNA amplicon sequencing reveals a polymicrobial nature of complicated claw horn disruption lesions and interdigital phlegmon in dairy cattle. Issue 1 (December 2018) - Bay, V.; Griffiths, B.; Carter, S.; Evans, N.; Lenzi, L.; Bicalho, R.; Oikonomou, G.
Abstract Lameness represents an intractable problem for the dairy industry. Complicated claw horn disruption lesions, interdigital hyperplasia, and interdigital phlegmon are important lameness causing foot lesions. Their aetiology is multifactorial, but infectious processes are likely implicated in disease pathogenesis. Our aim was to investigate the bacterial profiles of these lesions using 16S rRNA gene sequencing of samples obtained from 51 cattle across ten farms in the UK. In this study, interdigital hyperplasia, interdigital hyperplasia with signs of interdigital dermatitis, interdigital phlegmon, complicated sole ulcers, complicated toe ulcers lesions, and complicated white line lesions were investigated; corresponding healthy skin control samples were also analysed. All diseased tissues displayed reduced microbial richness and diversity (as described by Chao1, Shannon, and Simpson alpha-diversity indices) compared to their healthy skin control samples. Our results confirm the association ofTreponema spp with some of these disorders. Other anaerobic bacteria includingFusobacterium spp., Fastidiosipila spp. andPorphyromonas spp. were implicated in the aetiology of all these lesions with the exception of interdigital hyperplasia. Complicated claw horn disruption lesions, and interdigital phlegmon were found to have similar bacterial profiles. Such sharing of bacterial genera suggests many of the infectious agents detected in these foot lesions are acting opportunistically; this finding could contribute towards future treatment and control strategies.